María de la Cruz, el feminismo y el populismo peronista en Chile: María de la Cruz, feminism, and peronist populism in Chile (La Aljaba. Segunda Época. Revista de Estudios de la Mujer, 2025)
This articule will address the political career of María de la Cruz. She was an important figure of the Chilean mid-twentieth century because she was the first female senator elected in the Chilean history, but she was also controversial given her admiration for the Peronist regime, her attempts to replicate such ideology in Chile, and the corruption scandal which resulted in her early departure from parliament after only six months in that position. Her contradictions and impact on the Chilean political history, particularly on the history of Chilean feminism, will be studied through a review of her unpublished memoirs, interviews and press of her time.